Hemophagocytic lymphohistiocytosis in adults. Issue 3 (2nd July 2020) - Pandey, Yadav; Atwal, Dinesh; Konda, Manojna; Bimali, Milan; Middleton, Derek; Yarlagadda, Naveen; Firwana, Belal; Sasapu, Appalanaidu
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an underrecognized disorder due to the variability of its presentation and the fact that in adults, its diagnosis is based on cumbersome, pediatric-based criteria. Data regarding demographics, underlying causes, clinical features, laboratory results, complications, treatments received, and clinical outcomes were collected and analyzed in 41 patients who were diagnosed and treated at University of Arkansas for Medical Sciences between 2007 and 2019. In this group, 51% were male, the median age at diagnosis was 47 years, and 85% (35/41) met the HLH-2004 diagnostic criteria (5/8 variables). When evaluating seven extended variables easily obtained by routine laboratory test, 93% (38/41) of patients met 8 out of 15 criteria. The overall mortality in our patient population was 54% (22/41). The 30-day and 1-year overall survival estimates were 0.73 (95% confidence interval 0.56, 0.84) and 0.46 (95% confidence interval 0.29, 0.62), respectively. Thirty-five patients (85.4%) received HLH-directed therapy, and 19 patients (46.3%) achieved remission. The most common regimen for treating HLH was dexamethasone plus etoposide (53.7%). The patients with malignancy-related HLH had a worse prognosis than those without underlying malignancy, with a 73.33% (11/15) vs 34.62% (9/26) mortality ( P = 0.02). In conclusion, despite increasing recognition, HLH remains an enigmatic disorder with increased mortality, even more so with malignancy-associated HLH.